Racial criminalization of migrants in the 21st century - Palidda, Salvatore (Advances in criminology., 2011)
In the course of the last two decades, the number of arrests, imprisonment and detention of aliens and citizens of foreign origin has increased significantly in the West. This volume examines this growing trend towards racial criminalization and victimiza.